Ekoteologi dalam Perspektif Hadis Telaah Normatif terhadap Pembentukan Kesadaran Lingkungan - Sudirman; Muhammadiyah Amin; Abdul Rahman Sakka (STAI DDI Kota Makassar, 2026)
This study examines the concept of ecotheology from the perspective of Hadith, focusing on the contribution of the Prophet Muhammad’s teachings in fostering environmental awareness and ecological ethics. The research employs a normative approach by analyzing hadiths concerning tree planting narrated by Imam al-Bukhari, Muslim, al-Tirmidhi, Abu Dawud, al-Nasa’i, and Ibn Majah. The analysis covers the narrators (rawi), chains of transmission (sanad), and textual content (matan) to evaluate the authenticity and validity of these traditions as normative foundations for Islamic environmental ethics. The findings reveal that these hadiths are authentic (sahih), supported by continuous chains of transmission, reliable narrators, and consistent textual content that aligns with the principles of the Qur’an. The hadiths on tree planting emphasize that ecological activities possess spiritual value and constitute a form of ongoing charity (sadaqah), as their benefits extend to humans, animals, and other living beings. These findings demonstrate that Islam provides a strong theological foundation for environmental conservation through the concepts of khalifah (stewardship), amanah (trust), and ecological balance. Therefore, environmental hadiths remain highly relevant for addressing contemporary ecological crises and serve as a basis for developing Islamic environmental ethics oriented toward sustainability and ecological responsibility.